Maximizing the role of CSR amid the challenges of a pandemic - dina, Dina Amalia (Universitas Ahmad Dahlan, 2022)
The Covid-19 pandemic that hit almost all countries, including Indonesia brought many limitations in various fields or sectors in society. Starting from the social sector, transportation, manufacturing, food, to the economy. However, one of the sectors hardest hit by the pandemic is the economic sector. This happened because Indonesia implemented large-scale social restrictions, curfews, and even semi-lockdown which ultimately had an impact on the wheels of the economy not turning well. Deteriorating economic conditions, causing many companies to lose money. Companies that are still surviving are also facing new challenges, namely how to implement and maximize social obligations to the community even though the company's resources are limited. The purpose of this study is to find out how maximally Corporate Social Responsibility is carried out by companies and in this study, several companies with Corporate Social Responsibility activities will be explained during the pandemic.